Current routines for antibiotic prophylaxis prior to transrectal prostate biopsy – a national survey to all urology clinics in Sweden - Styrke, Johan (Umeå University, 2020)
Background: The risk of infection after transrectal ultrasound (TRUS)-guided prostate biopsies is increasing. The aim of the study was to assess the use of antibiotic prophylaxis for prostate biopsy in Sweden.

Methods: All public and private urology clinics reporting to the National Prostate Cancer Register of Sweden received a survey on TRUS-biopsy prophylaxis.

Results: Of the 84 clinics surveyed, 76 replied (90%). If no risk factors for infection were present, a single dose of ciprofloxacin 750 mg was used by 50 clinics (66%). Multiple doses of ciprofloxacin 500 or 750 mg (n=14; 18%) or a single dose of trimethoprim-sulfamethoxazole 160/800 mg (n=7; 9%) were other common prophylaxes. Most clinics gave the prophylaxes immediately before the biopsy (n=41; 54%). Urine dipstick was used by 30 clinics (39%) and rectal enema by six (8%). In patients with high risk of infection, the survey mirrors a large variety of regiments used.

Conclusions: The preference to use a single dose of ciprofloxacin 750 mg is in accordance with the Swedish national guidelines for patients with a low risk of infection. Better compliance to the guideline recommendation to use a urine dipstick would probably increase the number of patients classified as having an increased risk of infection. Being classified as a high-risk patient should lead to an extended duration of antibiotic prophylaxis, however, the variety of regimens used in the high-risk group reflects an inability to treat these patients in a standardized fashion and also highlights a need for more clear-cut guidelines. Pre-biopsy identification of high-risk patients is an important issue to tackle for the urologic clinics in order to reduce the number of infections.

Data are available under the terms of the Creative Commons Zero "No rights reserved" data waiver (CC0 1.0 Public domain dedication).

Survey data methodology
Current routines for antibiotic prophylaxis prior to transrectal prostate biopsy – a national survey to all urology clinics in Sweden

An electronic survey was distributed to all of the hospitals and outpatient urology clinics reporting to the national Swedish National Prostate Cancer Register (NPCR). The web-based Information Network for CAncer registers in Sweden (INCA) platform was used for reporting. Recipients of the survey were the trained staff reporting to the NPCR or the heads of department if contact with the staff could not be established. In one case, where neither of these recipients could be reached, the survey was distributed to a urologist known by the authors at the clinic in question. The questionnaires were distributed 2014-11-26 and after up to three reminders per e-mail, the last response was collected 2015-11-03. Data from the survey was downloaded into Microsoft Excel 2011 (Microsoft Corp., Redmond, WA) and exported to SPSS Statistics 23 (SPSS Inc., Chicago, IL) for further analysis.

Bakgrund: Under de senaste åren har det skett en riskökning för infektion efter prostatabiopsi. Målet med studien var att kartlägga användningen av antibiotikaprofylax vid prostatabiopsi i Sverige.

Metod: Alla enheter som rapporterar till nationella prostatacancerregistret fick en enkät om antibiotikaprofylax vid prostatabiopsi.

Resultat: Svarsfrekvensen var 90% (76 av 84 enheter). När det gäller patienter utan riskfaktorer för infektion var en enkeldos ciprofloxacin 750 mg den vanligaste profylaxen och användes av 50 enheter (66%). Fjorton enheter (18%) använde flera doser ciprofloxacin 500 eller 750 mg och sju enheter (9%) använde en singeldos av trimetoprim/sulfametoxazol 160/800 mg. När det gäller patienter med riskfaktorer för infektion (tex KAD eller tidigare urinvägsinfektion) visade enkäten ett vitt spektrum av olika preparat och behandlingslängder. Urinsticka användes av 30 kliniker (39%) och de flesta kliniker gav profylaxen omedelbart innan biopsin (n=41, 54%). Lavemang gavs av 6 enheter (8%).

Konklusion: Relativt god efterlevnad till nationella vårdprogrammet för prostatacancer visades för lågriskpatienter med hög användning av singeldos ciprofloxacin 750 mg. Emellertid visar de blandade svaren kring handläggning av riskpatienter att bristen på vägledning från nationella riktlinjer kan utgöra ett problem som leder till under- eller överbehandling. En ökad användning av urinsticka eller odling skulle kunna förbättra riskklassificeringen av patienter inför biopsi.

Data are available under the terms of the Creative Commons Zero "No rights reserved" data waiver (CC0 1.0 Public domain dedication).
Vilken typ av antibiotikaprofylax används vid prostatabiopsi i Sverige? - Enkät till alla enheter som rapporterar till Nationella prostatacancerregistret (NPCR)
Keywords: Antibiotic Prophylaxis; Antibiotikaprofylax; survey; undersökning; prostate biopsy; prostatabiopsi; prostate cancer diagnosis; prostatacancerdiagnos; Urology; Urologi